2017
DOI: 10.1038/s41467-017-00040-6
|View full text |Cite
|
Sign up to set email alerts
|

Intestinal microbial dysbiosis aggravates the progression of Alzheimer’s disease in Drosophila

Abstract: Neuroinflammation caused by local deposits of Aβ42 in the brain is key for the pathogenesis and progression of Alzheimer’s disease. However, inflammation in the brain is not always a response to local primary insults. Gut microbiota dysbiosis, which is recently emerging as a risk factor for psychiatric disorders, can also initiate a brain inflammatory response. It still remains unclear however, whether enteric dysbiosis also contributes to Alzheimer’s disease. Here we show that in a Drosophila Alzheimer’s dise… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
129
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 199 publications
(146 citation statements)
references
References 42 publications
6
129
0
1
Order By: Relevance
“…Wu et al . () validated the vascular hypothesis by indicating that vascular degeneration caused locomotor activities to decline in the Drosophila . Finally, upon investigating whether the enteric impairments induced neuroinflammation, they found that Aβ 42 transgenic Drosophila had upregulated TNF Eiger levels.…”
Section: The Changes In Gut Microbiome Composition In Neurodegeneratimentioning
confidence: 67%
See 2 more Smart Citations
“…Wu et al . () validated the vascular hypothesis by indicating that vascular degeneration caused locomotor activities to decline in the Drosophila . Finally, upon investigating whether the enteric impairments induced neuroinflammation, they found that Aβ 42 transgenic Drosophila had upregulated TNF Eiger levels.…”
Section: The Changes In Gut Microbiome Composition In Neurodegeneratimentioning
confidence: 67%
“…More recently, one study has indicated that cerebrovascular pathology can trigger tau pathology, and accumulation in the cortex appears to account for cognitive impairments (Kim et al 2018). Wu et al (2017) validated the vascular hypothesis by indicating that vascular degeneration caused locomotor activities to decline in the Drosophila. Finally, upon investigating whether the enteric impairments induced neuroinflammation, they found that Ab 42 transgenic Drosophila had upregulated TNF Eiger levels.…”
Section: Introductionmentioning
confidence: 89%
See 1 more Smart Citation
“…There is tremendous diversity among individuals’ intestinal microbiota with respect to the composition of specific bacterial species and the density (number) of bacteria that are present for each of these bacterial species. Indeed, such interpersonal differences in intestinal bacteria composition have been associated with the presence or absence of an increasing number of health issues, including metabolic syndrome, obesity, immunological diseases, cardiovascular diseases, as well as neuro-degenerative disorders such as Alzheimer’s disease (AD) and Parkinson’s disease (PD) [14]. …”
Section: Introductionmentioning
confidence: 99%
“…Measurement methods involved in were introduced from previously reported publications [12,13]. The Drosophila brains with different genetic backgrounds were live dissected and incubated with 10 μ M DCFDA for 5 min at RT if applicable, brain images were captured using a Leica TCS SP5 II confocal microscope with 488 nm excitation and 525 nm emission.…”
Section: Assessment Of Whole Brain Redox Statementioning
confidence: 99%